Parental Reflective Functioning as a Moderator of the Link Between Prematurity and Parental Stress - Dollberg, Daphna G.; Harlev, Yael; Malishkevitch, Sivan; Leitner, Yael (Frontiers in Psychiatry, 2022)
We examined group differences between parents, both mothers and fathers, of premature and full-term infants to determine whether they differed in their reports of subjective parenting stress and in their level of parental reflective functioning (PRF). We also tested whether each parent’s reflective functioning moderated the links between birth status (prematurity vs full-term) and parenting stress. A sample of 73 cohabiting, heterosexual Israeli families with a premature (28–36th week gestational age, N= 34) or full-term infant (37th week and above gestational age, N= 39) participated, comprising the two parents' groups. Infants’ age averaged 7.07 months (SD=1.28). Each parent completed the Parent Stress Inventory (PSI) individually to determine his/her subjective personal and childrearing stress levels. The Parent Development Interview (PDI-R2-S) was used to obtain each parent’s PRF (self and child/relation-focused) level. Findings showed that the premature and full-term parents did not differ in their PSI scores or PRF levels. However, mothers’ self-focused PRF moderated the link between prematurity and personal parenting stress, whereas fathers’ self-focused PRF moderated the link between prematurity and childrearing parenting stress. Furthermore, fathers’ and mothers’ PRF operated differently in the premature and full-term parents’ groups. The findings highlight the importance of mothers’ and fathers’ PRF in predicting parents’ subjective stress in general and particularly in the case of infant prematurity. We discuss these findings and their relevance for preventive and therapeutic perinatal interventions.